PERJUANGAN CIVIL SOCIETY DALAM MEMPERLUAS RUANG DEMOKRASI DI ASIA - Amal, M. Khusna (Jurnal Review Politik, 2013)
Even civil society was one requirement for the process of democratization, but it does not mean the existence of civil society automatically have a constructive impact to the democratization process. The assumption will be verifiable through qualitative analysis with descriptive analytic method. Experience of Indonesia, Philippines and South Korea showed that the changes of social-democratic politics, were determined by the role of civil society. However, the findings of this study indicate that proliferation of civil society in these countries has led to disagreement among the elements of civil society that have a negative impact for democratization. Thus, civil society can be a trouble maker for the process of democratization.